Prevalence of penile curvature: a population‐based cross‐sectional study in metropolitan and rural cities in Australia. (28th November 2018) - Chung, Eric; Gillman, Michael; Rushton, Derren; Love, Chris; Katz, Darren
Abstract : Objective: To evaluate the prevalence of penile curvature and health‐seeking behaviour in Australian men. Patients and Methods: A population‐based, cross‐sectional anonymous web‐based survey was designed, and men aged between 35 and 75 years in major and rural metropolitan cities across Australia were invited to participate. Respondents were screened for self‐reported symptoms of penile curvature and their impact on various psychosexual domains. Results: Of a total of 1782 men who responded, 333 men (19%) reported a bend or curve in their penis and completed the main section of the questionnaire to address the impact of penile curvature on various psychosexual domains. A third of men with penile curvature (32%) reported penile curvature of ≥ 30°, with approximately equal proportions among the three age groups (33% in those aged 35–49 years, 37% in those aged 50–64 years, and 30% in those aged 65–75 years) and with no significant difference detected in the penile curvature characteristics between men in major metropolitan and those in rural cities across Australia. One in six men reported an adverse impact of penile curvature in their lives, complaining of penile pain or discomfort when they had an erection, while 26% of men were bothered by the appearance of their penis and 20% were bothered when they tried to have sexual intercourse. Men aged 35–49 years were more likely than those aged 65–75 years to be bothered by the penile curvature (31% vs 18%; P < 0.05) and men in the age group 65–75 years were twice as likely to have trouble with sexual intercourse compared with other age groups (39% vs 18%; P < 0.05). Conclusions: This first population‐based study to estimate the prevalence of penile curvature in Australia highlighted that penile curvature is common and has a significant adverse impact on psychosexual functions.